2021
DOI: 10.1002/ldr.4031
|View full text |Cite
|
Sign up to set email alerts
|

A case‐study on history and rates of gully erosion in Northeast China

Abstract: Mollisols are of major importance for food security worldwide but are increasingly degraded by soil erosion. Mollisols in Northeast China have been converted into agricultural use only since the 19th century, but gullies are widely distributed. Gully erosion history, rates, and causes in this region remained unclear. We chose a study area with landforms and land-use history typical for the central Mollisol region of Northeast China to estimate the initiation years and rates of gully erosion from 1968 to 2018 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The same effect of abandoned field roads on gully development was found in Poland (Gardziel et al, 1998;Gardziel & Rodzik, 2001;Schmitt et al, 2006;Dotterweich et al, 2012;Rodzik et al, 2015), Slovakia (Stankoviansky, 2003), or China (Zhang et al, 2019;Wen et al, 2021). In eastern Poland, Rodzik et al (2015) and Szwarczewski et al ( 2020) also described gully incision as a combined effect involving the presence of an abandoned field road and fine sandy deposits, as is the case in the Fb gully.…”
Section: Discussionmentioning
confidence: 69%
“…The same effect of abandoned field roads on gully development was found in Poland (Gardziel et al, 1998;Gardziel & Rodzik, 2001;Schmitt et al, 2006;Dotterweich et al, 2012;Rodzik et al, 2015), Slovakia (Stankoviansky, 2003), or China (Zhang et al, 2019;Wen et al, 2021). In eastern Poland, Rodzik et al (2015) and Szwarczewski et al ( 2020) also described gully incision as a combined effect involving the presence of an abandoned field road and fine sandy deposits, as is the case in the Fb gully.…”
Section: Discussionmentioning
confidence: 69%
“…It is generally found that human activities accelerated gully erosion mainly by destroying vegetation and changing land use (Kang, Wang, et al, 2021; Poesen, 2018; Shellberg, 2021; Wen et al, 2021). But in this research, human activities reduced the gully quantitative characteristics of AF to a certain extent (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Gully development includes headcut retreat, sidewall collapse, and bed downcutting (Harvey, 1992). Gully erosion is affected by many influencing factors, including soil, lithology, climate, topography, vegetation, and human activities (Kang, Wang, et al, 2021; Poesen, 2018; Shellberg, 2021; Wen et al, 2021). As the materials of gully erosion, soil and lithology determine the erodibility (Poesen, 2018; Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Mollisols area of northeast China (NEC), as one of the four largest mollisols regions globally, and is the base of grain production in China [34], but it is being restricted by gully erosion [35]. At present, there are 296,000 gullies in the Mollisols area of NEC [36,37], of which 89% of the gullies are still in the developing stage, and gully erosion has damaged up to 2.2 × 10 5 ha of land that accounts 0.4% of the total area of NEC, indicating that the gully erosion rate is high and that its risk extended gradually [38].…”
Section: Introductionmentioning
confidence: 99%